The right to do wrong morality and the limits of law - Osiel, Mark (Harvard University Press, 2019)
The law sometimes permits what ordinary morality, or widely-shared notions of right and wrong, reproaches. Rights to Do Grave Wrong explores the relationship between law and common morality to clarify law's reliance on society's broad presumption that people will exercise their rights responsibly. More concretely, he argues that certain legal rights rest on tacit sociological assumptions as to who will exercise them, under what circumstances, and how frequently. Further, he argues that we depend on stigma and shame to reduce and circumscribe the law's use. Some examples: though reneging on a debt is considered wrong, the law allows you to declare personal bankruptcy; international law allows museums to retain some masterworks looted from their rightful owners; in many countries abortion is permitted as a means of birth control. Using these examples and more, Osiel presents a "social scientific" analysis of law's interaction with social mores and the extent to which they limit our exercising rights to do wrong. The paradox he intends to elucidate is when and why it is appropriate for societies to champion de jure entitlements even as they successfully limit their de facto usage.--